Superior Lateral Genicular Artery Perforator Flap for Soft Tissue Coverage around knee: Clinical Experience at CMCH (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Background: Knee joints play an important role in gait and weight bearing. So reliable knee joint coverage is essential for recovery of the most function of lower limb. Among a variety of reconstructive options for the knee the Lateral Genicular artery Perforator Flap is reliable method in soft-tissue cover around the knee with an excellent outcome and minimal morbidity of the donor site. The vascular basis of this flap has consistent and reliable anatomy.  So the present study observes the outcome of superior lateral genicular artery flap for soft tissue defect around the knee.Material & Methods: This study was done at the department of Plastic and Reconstructive Surgery, Chittagong Medical College Hospitals, from January 2020 to July 2023. It included 18 patientsResult: Among 18 patients male were predominant with their age ranged from 15 to 60 years. The knee defects were due to different etiologies maximum patients (12) were patients with road traffic accidents. The defects were covered by the superior lateral genicular artery perforator flap all flaps survived except in 3 cases. 2 cases managed conservatively and healed well and in the third case the necrotic part was debrided and skin grafted.  The donor site was closed primarily in 12 cases and skin grafted in 6 cases.Conclusion: Superior Lateral genicular artery perforator flap is a good option for cover of soft tissue defects around the knee . The anatomy of the flap perforators is consistent and reliable.  Donor site morbidity is minimal with no functional loss.J Bangladesh Coll Phys Surg 2026; 44: 83-87